Functionalized Gold Nanoclusters Promote Stress Response in COS‐7 Cells. Issue 4 (5th February 2023) - Linklater, Denver P.; Le Guével, Xavier; Kosyer, Erim; Rubanov, Sergey; Bryant, Gary; Hanssen, Eric; Baulin, Vladimir A.; Pereiro, Eva; Perera, Palalle G.Tharushi; Wandiyanto, Jason V.; Angulo, Ana; Juodkazis, Saulius; et al.
Abstract : Ultrasmall gold nanoclusters (AuNC) show great promise for application in theranostics due to their unique optical and physicochemical properties; however, the associated nanotoxicology concerns need to be carefully considered because of their high diffusion across the cellular barrier. Herein, new insights into the role of surface modification of 2 nm AuNC on their toxicity with impact on the metabolism of COS‐7 fibroblast‐like cells are revealed. AuNCs are chemically modified with either a monodentate‐thiolated molecule (AuNC‐MHA) or a modified‐bidentate sulfobetaine zwitterionic molecule (AuNC‐ZwBuEt). Uptake and localization inside fibroblasts and the resultant influence on cell ultrastructure are carefully evaluated using scanning transmission electron microscopy (STEM) and cryo‐soft‐X‐ray tomography (cryo‐SXT). At concentrations of ≥25 μg Au mL −1, AuNC‐ZwBuEt are cytotoxic toward COS‐7 cells and are observed to cross the nuclear membrane. Cryo‐SXT analysis shows that fibroblasts develop an acute stress response in the form of swollen mitochondria, nuclear membrane blebbing, and large cytoplasmic vacuoles as early as 1 h postexposure. By contrast, AuNC‐MHA are not cytotoxic toward COS‐7 cells. Endosomal escape and translocation of the AuNC‐ZwBuEt into the nucleus and other organelles may be the cause for the observed cytotoxicity and highlight the need for further study of metal nanocluster‐cell interactions. Abstract : AuNC cytotoxicity toward COS‐7 fibroblasts is revealed as a result of change in particle hydrophobicity. Single AuNCs are found localized to the nucleus after 24 h exposure, and cryo‐SXT analysis shows severe cell stress response in the form of swollen mitochondria, nuclear membrane blebbing, and the formation of large vacuoles.